2019
DOI: 10.1371/journal.pone.0217970
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic effects of perceived social support on family health and family functioning in patients with heart failure and their nearest relatives: Using the Actor–Partner Interdependence Mediation Model

Abstract: Background Social support, family functioning and family health are essential elements in the treatment of heart failure, yet most heart failure studies focus on the pharmacological interventions. This study aimed to examine whether perceived social support from nurses is associated with better family functioning of patients with heart failure and their nearest relatives and to examine whether family health mediates this relationship. Methods and findings A sample of 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
(54 reference statements)
1
20
0
2
Order By: Relevance
“…There are two possible reasons. One reason may be that social support improves an individual's physical health (for example, by increasing healthy activities and protective behaviours and promoting a healthier lifestyle) and ability to manage their stress and cope effectively; accordingly, the individual functions better within the family [61]. The other reason may be that the family members provide the most solid support in one's social network [62], partly owing to Chinese culture-specific norms of reciprocal filial piety [63], therefore, good social support means good family function in Chinese societies.…”
Section: Discussionmentioning
confidence: 99%
“…There are two possible reasons. One reason may be that social support improves an individual's physical health (for example, by increasing healthy activities and protective behaviours and promoting a healthier lifestyle) and ability to manage their stress and cope effectively; accordingly, the individual functions better within the family [61]. The other reason may be that the family members provide the most solid support in one's social network [62], partly owing to Chinese culture-specific norms of reciprocal filial piety [63], therefore, good social support means good family function in Chinese societies.…”
Section: Discussionmentioning
confidence: 99%
“…There are two possible reasons. One reason may be that social support improves an individual's physical health(e.g., increases healthy activities and protective behaviours and promoting a healthier lifestyle) and ability to manage their stress and cope effectively; accordingly, the individual functions better within the family [63]. The other reason may be that the family members provide the most solid support in one's social network [64], partly owing to Chinese culture-speci c norms of reciprocal lial piety [65], therefore, good social support means good family function in Chinese societies.…”
Section: Discussionmentioning
confidence: 99%
“…Significant improvements in scores regarding health promoting ( activities ) and well‐being may reflect perception of improved reinforcement and capability of decision‐making. Similarly, a recent study has revealed that patients with HF and their family members who considered increased social support from nurses indicated high level of family health and improved function in the family (Shamali et al, 2019). Future studies should address this dynamic interaction (Chung et al, 2009).…”
Section: Discussionmentioning
confidence: 98%